2023
DOI: 10.5603/demj.a2023.0009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disturbances among emergency response team paramedics working in shift systems

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Insomnia, characterized by difficulty in initiating and maintaining sleep, is a common complaint among shift workers, including paramedics. 4 In Saudi Arabia, where the healthcare system is rapidly evolving, the prevalence of insomnia among paramedics has not been extensively studied. This gap highlights the need for targeted research to understand the magnitude and characteristics of insomnia in this specific demographic, considering cultural, environmental, and occupational factors unique to the region.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia, characterized by difficulty in initiating and maintaining sleep, is a common complaint among shift workers, including paramedics. 4 In Saudi Arabia, where the healthcare system is rapidly evolving, the prevalence of insomnia among paramedics has not been extensively studied. This gap highlights the need for targeted research to understand the magnitude and characteristics of insomnia in this specific demographic, considering cultural, environmental, and occupational factors unique to the region.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that there is a positive relationship between the measured level of employee engagement and business unit outcomes such as higher productivity, better quality, lower employee turnover, greater customer satisfaction, and increased profitability [11,12]. In addition, there are studies in the literature that reveal the relationship between occupational safety performance and employee engagement [13,14]. In these studies, it is seen that people who experience fewer work accidents have more work engagement.…”
Section: Introductionmentioning
confidence: 99%